LoRa and LoRaWAN in the IoT: Performance, Challenges, and Future Opportunities - Shravani Pimpodkar; Yogesh Nazarkar; Nandini Dhole; Tulsi Patil; Geetanjali Suryawanshi (International Journal of Wireless Security and Networks, 2026)
This paper provides a broad overview of both LoRa and LoRaWAN technologies in the context of Internet of Things (IoT). The market need for communication technology to be low-power and long-range continues to grow, and LoRa and LoRaWAN are emerging as viable options for enabling widespread IoT applications in a variety of applications. This review offers structured and comparative assessment of their functionality in different environments, such as urban, rural, suburban and forest environments. These key communication parameters are discussed extensively and their effects on system performance are analyzed, including spreading factor, bandwidth, coding rate, transmission range, energy consumption, and network scalability. Additionally, the study thoroughly examines the latest developments in energy efficient communication technologies, adaptive data rate schemes, network optimization strategies and intelligent approaches using artificial intelligence (AI) to enhance resource utilization and communication reliability. The review also delves into the key challenges of LoRa and LoRaWAN networks, such as interference, network congestion, duty cycle, security, and scalability. The results of the literature review indicate that there are several areas of research that have not been addressed and further research is suggested. This includes the creation of hybrid communication architectures, integration with edge and cloud intelligence, cross-layer optimization frameworks, advanced security mechanisms, and the implementation of AI-based adaptive networking strategies. The findings reported in this work can help researchers, practitioners, and system designers to improve their understanding of capabilities, limitations, and future potential of LoRa and LoRaWAN technologies, offering guidance to their design.
Keywords: Adaptive Data Rate; Chirp Spread Spectrum (CSS); Communication Performance; Energy optimization; Internet of Things; LoRa; LoRaWAN; Low Power Wide Area Network (LPWAN); wireless communication